Storja ta' Malta - Pace, Tony (Directorate for Quality and Standards in Education, Curriculum Management and eLearning Department, 2009)
"The author takes a look at everything that happens in Malta at the time when the Maltese Islands were conquered by the Knights of St. John. It is a very important period during which the foundations of modern Malta were laid. here we have a book that is not just a narrative or a research, a book whose ultimate goal is for students to be able to acquire the skills needed to know what Malta has gone through over the ages." -- Raymond J. Camilleri, Director of Curriculum and eLearning (Page III, aus dem Maltesischen übersetzt)